Application of Problem-Based Learning (PBL) Model and Project-Based Learning (PJBL) in Learning Mathematics in Elementary Schools - Zulfah Adiatmah Nauap; I Wayan Widana (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to develop and implement Problem-Based Learning (PBL) and Project-Based Learning (PJBL) learning models in mathematics learning at SD Negeri No. 18 Bababulo, Majene Regency. The main objective of implementing these two models is to increase student involvement, as well as critical, analytical, and creative thinking skills in solving mathematical problems. The implementation procedure began with an introduction to the theme of the impact of plastic waste on the environment. Students were divided into six groups to discuss problems, develop project plans, and conduct observations. The results showed that students were actively involved, with significant increases in motivation and critical thinking skills. Enthusiasm was seen during discussions and presentations, although there were challenges related to self-confidence during presentations, which were overcome through practice from the teacher. The conclusion of this study states that the implementation of PBL and PJBL is effective in improving students' understanding of mathematical concepts and social skills. Suggested follow-ups include consistent implementation of both models and periodic evaluation to improve the quality of learning.